PERAN INTERNATIONAL COURT OF JUSTICE (ICJ) DALAM PENYELESAIAN SENGKETA BATAS MARITIM ANTARA SOMALIA DAN KENYA DI SAMUDRA HINDIA TAHUN 2017-2021 - Laras Sulistiowati (2024)
This research aims to describe the role of the International Court of Justice (ICJ) as an international organization in resolving maritime boundary disputes between Somalia and Kenya in the Indian Ocean during the period 2017-2021. The study utilizes the theory of international organization roles and the concept of maritime delimitation to elucidate the ICJ's role in settling the maritime boundary dispute between Somalia and Kenya in the Indian Ocean. This qualitative research relies on literature review as the data collection technique. Primary data sources are obtained from the official ICJ website, while secondary data sources are derived from related research on the ICJ's role and published cases of the Somalia-Kenya dispute. The acquired data is then analyzed through data reduction, data presentation, and drawing conclusions. The research findings indicate that the ICJ plays its role as an independent arena and actor. The ICJ serves as a forum for the resolution of maritime boundary disputes between Somalia and Kenya. The ICJ's decisions refer to the United Nations Convention on the Law of the Sea (UNCLOS) as international law and customary international law, ensuring that they are not influenced by other states or external powers. Through its rulings, the disputed areas have been determined based on international legal provisions and customary international practices. The absence of conflict indicates that the ICJ has successfully resolved the maritime boundary dispute peacefully.